2022
DOI: 10.1038/s41598-022-13233-x
|View full text |Cite
|
Sign up to set email alerts
|

Developing an accurate empirical correlation for predicting anti-cancer drugs’ dissolution in supercritical carbon dioxide

Abstract: This study introduces a universal correlation based on the modified version of the Arrhenius equation to estimate the solubility of anti-cancer drugs in supercritical carbon dioxide (CO2). A combination of an Arrhenius-shape term and a departure function was proposed to estimate the solubility of anti-cancer drugs in supercritical CO2. This modified Arrhenius correlation predicts the solubility of anti-cancer drugs in supercritical CO2 from pressure, temperature, and carbon dioxide density. The pre-exponential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…Furthermore, it is found that less than 7.5% of the literature data are suspect information, and the remaining 92.5% are valid measurements. (4)…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is found that less than 7.5% of the literature data are suspect information, and the remaining 92.5% are valid measurements. (4)…”
Section: Discussionmentioning
confidence: 99%
“…The stratum corneum, composed of corneocytes and a lipid-rich matrix, serves as the skin’s principal barrier (chain ceramides, free fatty acids, and cholesterol). It blocks the skin’s ability to take hydrophilic or macromolecular drugs [ 35 ]. As the stratum corneum is impenetrable for most drugs, a biochemical strategy is needed to transport both hydrophilic and hydrophobic therapeutic molecules into the skin, and lipid-based nano-drug delivery devices are one such method.…”
Section: Mechanism Of Lipid-based Drug Delivery Systemsmentioning
confidence: 99%
“…Moreover, they have great potential to be used in DDS via skin for transdermal drug delivery applications. In addition, hydrogels may be able to sustain the release of drugs when they are utilized in tissue engineering and cancer therapy [80]. This shows that hydrogels can be considered a perfect-matched option for use in various fields such as anticancer drugs, contact lenses, regenerative medicine, tissue engineering, barrier material to regulate adhesions, food packaging, and controlled DDS that derives from the high water content and hydrophilic nature of hydrogels.…”
Section: Biomedical Applications Of Polysaccharide-based Hydrogelsmentioning
confidence: 99%